Synthesis, crystal structures, and electronic properties of one dimensional Ba9Sn3(Te1−xSex)15 (x = 0–1). Issue 8 (11th July 2017) - Zhang, Jun; Su, Rui; Wang, Xiancheng; Li, Wenmin; Zhao, Jianfa; Deng, Zheng; Zhang, Sijia; Feng, Shaomin; Liu, Qingqing; Zhao, Huaizhou; Guan, Pengfei; Jin, Changqing
Abstract : The new semiconducting compounds Ba9 Sn3 (Te1− x Se x )15 synthesized under high pressure and high temperature are constructed with trimeric SnTe/Se6 octahedron chains. Abstract : In this work, the Ba9 Sn3 Te15 compound has been synthesized for the first time under high pressure and high temperature conditions. Single-crystal X-ray diffraction analysis shows that Ba9 Sn3 Te15 crystallizes into a hexagonal structure with a space group of P 6̄ c 2 (188) and lattice parameters of a = b = 10.2403(1) Å, and c = 20.7720(2) Å. The crystal structure contains trimeric one-dimensional chains with face-sharing SnTe6 octahedrons stacked along the c -axis. These chains are arranged in a triangular lattice in the ab plane. The energy dispersive X-ray spectroscopy measurement for a single crystal of Ba9 Sn3 Te15 shows approximately 6% vacancies on the Sn sites. The anion Te can be substituted by Se to form Ba9 Sn3 (Te1− x Se x )15 with x = 0–1. The resistivity and Seebeck coefficient measurements were performed. Ba9 Sn3 Te15 behaves similar to a semiconductor with a band gap of approximately 24 meV. When Se is doped, the resistivity increases and the band gap is enhanced to 508 meV for x = 1. The Seebeck coefficient ranges from 31 μV K −1 to 90.7 μV K −1 . Ab initio calculations were also performed to study the density of states and band structures for Ba9 Sn3 Te15 and Ba9 Sn3 Se15 .